2001
DOI: 10.1002/jmv.2065
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and cytokine production gauge response of patients with hepatitis C to interferon‐α therapy

Abstract: Interferon is the primary treatment for hepatitis C virus (HCV). However, the long-term success rate is low particularly for African Americans relative to Caucasians and may be due to differential immune abilities. This study compared cytokine production from PHA-stimulated peripheral blood from 25 healthy and 40 HCV-infected African Americans and Caucasians. HCV patients were designated as IFN responders or nonresponders based on outcome after therapy. Ethnicity and genotype were associated with IFN response.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
2
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 41 publications
1
46
2
1
Order By: Relevance
“…The Asian population showed more G allele frequency than Caucasians [19,26,27]. In line with those reports, interethnic variation has recently been reported in the production of cytokine and immune response between different ethnic origins [28]. Regarding the issue of sample size, although our sample with BID had a power of 0.80 to detect a small ES (w = 0.14), corresponding to a difference of 13% between the two alleles, in future study, the sample size should be increased in order to exclude type II error.…”
Section: Discussionsupporting
confidence: 82%
“…The Asian population showed more G allele frequency than Caucasians [19,26,27]. In line with those reports, interethnic variation has recently been reported in the production of cytokine and immune response between different ethnic origins [28]. Regarding the issue of sample size, although our sample with BID had a power of 0.80 to detect a small ES (w = 0.14), corresponding to a difference of 13% between the two alleles, in future study, the sample size should be increased in order to exclude type II error.…”
Section: Discussionsupporting
confidence: 82%
“…The causes of racial variation are still unclear. Some factors, like cytokine production and hepatic iron level, have been considered as the origin of inter-ethnic differences in prior investigations [41,42]. Since the strong associations of IL28B gene polymorphisms with HCV clearance have been demonstrated, SNPs near the IL28B gene are thought to be the leading cause of racial variation of HCV clinical outcomes [43].…”
Section: Discussionmentioning
confidence: 99%
“…Further, viral kinetics studies have shown that African Americans exhibit significantly lower interferon effectiveness and achieve a lower reduction in HCV RNA in the first 24 h of treatment [29] . It was also noted that African Americans had different pretreatment cytokine profiles [30] . In addition, while they mounted a more robust HCV-specific CD4 Th1 proliferative response, it did not translate into a higher rate of IFN-gamma production, potentially secondary to their dysfunctional nature, which was associated with a failure of interferon therapy [31][32] .…”
Section: Discussionmentioning
confidence: 99%